(untitled) (Research, Society and Development, 2020)
Objective: To identify socioeconomic factors and gastrointestinal disorders associated with the use of non-steroidal anti-inflammatory drugs in patients with dyspeptic symptoms. Method: Cross-sectional study, carried out with 751 patients seen at a public endoscopy service. The association between socioeconomic factors and gastrointestinal disorders with the use of non-steroidal anti-inflammatory drugs was verified using Pearson’s correlation tests and measuring their effect using the odds ratio. The research was approved by the Ethics Committee on Research with Human Beings, according to opinion No. 1,304,308. Results: The prevalence of the use of non-steroidal anti-inflammatory drugs was 57.1%. There was an association between the use of non-steroidal anti-inflammatory drugs and smoking (RC: 1.85; p = 0.002), alcoholism (RC: 1.46; p = 0.01), H.pylori infection (RC = 0 , 75; p = 0.036) and with peptic ulcer disease (RC: 2.29; p = 0.005). Conclusions: The study showed that the use of non-steroidal anti-inflammatory drugs is frequent in patients who seek the endoscopy service. Smoking and alcoholic patients were more likely to use these drugs and their use increase the chances of developing peptic ulcers.